Adaptive E-Learning for the Engineering Design Education at Ruhr-University Bochum. (May 2022) - Kossack, F.; Kattwinkel, D.; Bender, B.
Abstract: Most lectures in the field of engineering are held in a traditional teacher-centred and frontal lecture format. This means that all students receive the identical information at the same pace without taking their individual skills, knowledges and competences into account. A didactic concept, that fosters an individual learning experience and digitally provides personalised learning materials for each student is Adaptive E-Learning. Within this paper the development of an Adaptive E-Leaning Environment in the course Engineering Design at Ruhr-University Bochum is presented.